Detection of Near- and Far-Field Traveling Ionospheric Disturbances During Tsunami Events over South Pacific - Castillo-Rivera, C (Elsevier Ltd, 2025)
Large earthquakes and tsunamis often occur around the Pacific Ring of Fire, in which Traveling Ionospheric Disturbances (TIDs) have been observed after these events. Sometimes (depending on seismic source features), TIDs can be observed near the epicenter of the generated earthquake due to the shock-acoustic wave. Additionally, TIDs can be induced by tsunamis due to the generated gravity waves and be detected several thousand kilometers away from the source. TIDs can be detected by analyzing Total Electron Content (TEC), which is calculated, indirectly, using signals from Global Navigation Satellite System (GNSS) receivers. The procedure allows for studying the ionospheric disturbance with a good spatial and temporal resolution. This study aims to identify tsunami-induced TIDs in the near- and far-fields following significant events in the Oriental and Occidental South Pacific Ocean. The selection criteria covering 14 tsunamis that occurred between 2010 and 2021 generated by earthquakes with Mw ⩾7.8 and depth less than 50 km. Tsunamis were modeled and compared with the TIDs obtained from TEC deviations. Near-field and far-field TIDs observed in hodochrons differ primarily in the clarity of their association with tsunamis. The simulated tidal gauges show a possible connection with the observed TEC anomalies, behaving similarly but with different delay times, showing some events even hours in advance. This potential correlation between TID parameters and tsunamis propagated in the Pacific Ocean can contribute to understanding the involved mechanisms and facilitate the development of near real-time early warning systems. © 2024 COSPAR